UPAYA PENDIDIKAN ANTI KORUPSI PADA GENERASI MUDA: FOKUS PADA REMAJA DAN SANTRI - Toufan Aldian Syah; Mujiningsih, Mujiningsih; Solihatin, Rina; Nengsi, Apriana; Akmal, Fakhrudin; Ajie, Eric Setia Permana (Al Jabiri: Jurnal Ilmiah Studi Islam, 2022)
Corruption is a severe problem Indonesia faces and needs to be resolved with an extraordinary approach. Instilling an anti-corruption attitude among youth and students can help form a generation with integrity and the character of honesty, intelligence, consistency, courage in upholding the truth, and confidence in conveying what is true according to Shari'a rules. This study aims to explain the strategy of instilling an anti-corruption attitude among santri. The method used is library research with a literature review technique. This study's results explain that to realize good anti-corruption education, there needs to be a collaboration between parents, educators, and the government so that awareness of the dangers and effects of corruption can be prevented from an early age. Prohibition of corruption is not only based on state law but also prohibited by Islamic law. Therefore, instilling Islamic values such as honesty, caring, and independence in students and youth can help shape anti-corruption character in society